The Effectiveness of a Proposed Strategy Based on the Twenty Thinking Keys in Developing Reading Comprehension among Fifth Preparatory Grade Students (Journal of the College of Basic Education, 2026)
This research aims to build a proposed strategy according to the twenty thinking keys in developing reading comprehension among fifth grade preparatory students, and to identify the effectiveness of the proposed strategy.To achieve the objectives of the research, the two researchers followed the procedures of the descriptive method in building the experiment and the procedures of the experimental method in the experiment. The two researchers prepared a proposed strategy to verify the research procedures, and the two researchers adopted an experimental design. The research population consisted of (1310) students. The sample was randomly selected, consisting of (46) students for the experimental group and (47) students for the control group, bringing the research sample to (93) students. The two researchers matched the two research groups in age in months, previous achievement, language ability test, intelligence test, and reading comprehension test. The two researchers prepared a test to measure reading comprehension skills, consisting of (26) items. The validity and reliability of the test and its psychometric characteristics were verified. After applying it and using the(SPSS) program, the two researchers reached the superiority of the students of the experimental group over the students of the control group in the reading comprehension skills test, as well as the effectiveness of the proposed strategy. The two researchers concluded that the proposed strategy proved its effectiveness in developing reading comprehension skills among fifth grade preparatory students, because it is characterized by deep understanding and motivation for learning. They recommended several recommendations, including: encouraging students to understand, settingobjectives and activities that make the student the focus of the educational process.They also proposed several suggestions, including conducting a similar study to identify the effectiveness of a proposed strategy in developing literary analysis skills at the preparatorn stage.